The complete mitochondrial genome of the Border Collie dog. (2nd January 2016) - Wu, An-Quan; Zhang, Yong-Liang; Li, Li-Li; Chen, Long; Yang, Tong-Wen
Abstract: Border Collie dog is one of the famous breed of dog. In the present work we report the complete mitochondrial genome sequence of Border Collie dog for the first time. The total length of the mitogenome was 16, 730 bp with the base composition of 31.6% for A, 28.7% for T, 25.5% for C, and 14.2% for G and an A–T (60.3%)-rich feature was detected. It harbored 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes and one non-coding control region (D-loop region). The arrangement of all genes was identical to the typical mitochondrial genomes of dogs.